Prevalence of high-risk human papillomavirus DNA and mRNA and its association with abnormal anal cytology in the Czech male anal cancer screening cohort - Nemcova, Jana; Cerna, Katerina; Rob, Filip; Smahelova, Jana; Tresnak Hercogova, Jana; Marx, Josef; Traxmandlova, Iva; Ondic, Ondrej (Diagnostic cytopathology, 2021)
BACKGROUND: Anal cancer (AC) screening is justified in high-risk populations, particularly HIV-positive men having sex with men (MSM). HR-HPV testing could improve the efficiency of cytologically based screening of AC, as in the screening of biologically analogical cervical cancer. The specificity of HR-HPV testing is influenced by the prevalence of HR-HPV infection in the screened population. Reported anal HR-HPV DNA prevalence in MSM is high, but HR-HPV mRNA reflects rather long-term infections and is more specific for high-grade lesions. However, no data were published about HR-HPV DNA and mRNA prevalence in the Czech AC screening population. METHOD: Results of liquid-based anal cytology of 203 predominantly HIV-positive MSM from the Czech AC screening cohort were correlated with results of DNA and E6/E7 mRNA testing of 14 HR-HPV types, and HPV16 genotyping. Eighty-one MSM underwent a standard anoscopy. RESULTS: A total of 109 (53.7%) samples had abnormal cytology, with 12 (5.9%) ASC-H/HSIL, 67 (33.0%) samples cytologically negative, and 27 (13.3%) unsatisfactory. HR-HPV DNA was detected in 134 (66.0%) and HR-HPV RNA in 72 (35.5%) anal smears. HR-HPV mRNA and HPV16 mRNA positivity were associated with abnormal cytology (p = .0037, p = .0021). No significant association was found between HR-HPV DNA or HPV16 DNA positivity and abnormal cytology. No high-grade lesions were revealed by anoscopy. CONCLUSION: Prevalence of anal HR-HPV DNA among Czech MSM is high, however, the prevalence of HR-HPV mRNA is half and associated with abnormal cytology. Our results indicate an increased efficiency of cytological screening when combined with HR-HPV mRNA testing.
Keywords: dospělí; Female; Papillomavirus Infections; časná detekce nádoru; Prevalence; Homosexuality, Male; Adult; mladý dospělý; Anus Neoplasms; ženské pohlaví; DNA, Viral; lidé; Sexual and Gender Minorities; homosexualita mužská; messenger RNA; RNA, Messenger; Humans; prevalence; Male; Czech Republic; Young Adult; infekce papilomavirem; Česká republika; Early Detection of Cancer; lidé středního věku; sexuální a genderové menšiny; mužské pohlaví; Middle Aged; DNA virů; nádory anu